COMPUTER TASK FOR ASSESSMENT AND TRAINING OF ATTENTION: APPLICATION IN SPORT TRAINING - Hernández Mendo, Antonio; Ramos Pollán, Raúl (Anales de Psicología / Annals of Psychology)
In this research we present a new the computerized version of the grid exercise, its management and its funcional values.This software allows evaluation and trainning of wide and narrow external attention; according to Nideffer and Sharpe's (1978) ACT's basic postulates.This program, implemented under windows –a multitasking environment- specially allows presentation of stimulus ocupying two sensorial channels. Besides, this design allows the use of distractor stimulus and rythym's kinesiological interiorization.We finish showing the applications of this computerized task within the field of sports psychology applied to trainning and competition.